2014
DOI: 10.1007/s00792-013-0617-6
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of bacterial diversity associated with microbial mats, gypsum evaporites and carbonate microbialites in thalassic wetlands: Tebenquiche and La Brava, Salar de Atacama, Chile

Abstract: In this paper, we report the presence of sedimentary microbial ecosystems in wetlands of the Salar de Atacama. These laminated systems, which bind, trap and precipitate mineral include: microbial mats at Laguna Tebenquiche and Laguna La Brava, gypsum domes at Tebenquiche and carbonate microbialites at La Brava. Microbial diversity and key biogeochemical characteristics of both lakes (La Brava and Tebenquiche) and their various microbial ecosystems (non-lithifying mats, flat and domal microbialites) were determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

16
127
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(146 citation statements)
references
References 81 publications
16
127
1
2
Order By: Relevance
“…The high concentration of arsenic present in HAAL is strongly limiting not only for human life but also for growth of many microorganisms (Valko et al, 2005) and selects development of arsenic tolerant bacteria (Dib et al, 2008;Ordoñez et al, 2009). Different concentrations of arsenic (maximum values) were reported in these environments, 2.3 mg L −1 in Tebenquiche Lake (Farías et al, 2014), 9.1 mg L −1 in Salar de Llamara , 0.8-11.8 mg L −1 in Andean Lakes , 0.9-28 mg L −1 in salt lakes (Lara et al, 2012). Recently, in other HAAL higher values were detected, namely arsenic values between 18.5 and 33.8 mg L −1 were observed in Laguna Socompa ; these values are greater than the one reported for Mono Lake (200 µM HAsO −2 4 , approximately 19.8 mg L −1 As) (Oremland et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The high concentration of arsenic present in HAAL is strongly limiting not only for human life but also for growth of many microorganisms (Valko et al, 2005) and selects development of arsenic tolerant bacteria (Dib et al, 2008;Ordoñez et al, 2009). Different concentrations of arsenic (maximum values) were reported in these environments, 2.3 mg L −1 in Tebenquiche Lake (Farías et al, 2014), 9.1 mg L −1 in Salar de Llamara , 0.8-11.8 mg L −1 in Andean Lakes , 0.9-28 mg L −1 in salt lakes (Lara et al, 2012). Recently, in other HAAL higher values were detected, namely arsenic values between 18.5 and 33.8 mg L −1 were observed in Laguna Socompa ; these values are greater than the one reported for Mono Lake (200 µM HAsO −2 4 , approximately 19.8 mg L −1 As) (Oremland et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have investigated species compositions in soils of extreme environments (Bontognali et al 2010(Bontognali et al , 2012Farías et al 2014;Jay et al 2014); however, most of these have focused on the top layers or subsurface of soils from areas such as hypersaline sediments and Sabkhas (Kjeldsen et al 2007;Abdeljabbar et al 2013;Al-Najjar et al 2014), or saline/soda lakes (Sorokin et al 2014). In such environments, the biogeochemical cycle of nitrogen and sulphur is very important and shapes the microbial communities (Oren 2008;Al-Thani et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, many studies have investigated the Atacama Desert (Desierto de Atacama) located as a plateau in South America along the Pacific coast to the west of the Andes mountains. It is the driest, non-polar and oldest desert on Earth (Farías et al 2014;Rasuk et al 2014Rasuk et al , 2016. Recent findings (Rasuk et al 2016) have indicated that a large proportion of 16S sequences could not be classified at the phylum level, which may indicate a new phylum is present in this Desert.…”
Section: Introductionmentioning
confidence: 99%
“…The salt composition is dominated by sulfate, chloride, sodium, and divalent cations [3] [5]. In spite of all of this, phototrophic and heterotrophic bacteria have recently been found in halite and gypsum evaporites and microbial mats [5] [6].…”
Section: Introductionmentioning
confidence: 99%
“…These ecosystems are characterized by extreme aridity, strong winds, scarce but torrential rainfall, high rates of evaporation, high solar radiation, extreme daily temperature changes, negative water balance, combined with a wide range of salinity [1] [3] [4]. The salt composition is dominated by sulfate, chloride, sodium, and divalent cations [3] [5]. In spite of all of this, phototrophic and heterotrophic bacteria have recently been found in halite and gypsum evaporites and microbial mats [5] [6].…”
Section: Introductionmentioning
confidence: 99%